Clinical and echocardiographic features of platypnea-orthodeoxia syndrome: a single-centre experience. (4th February 2022) - Fialho, I; Passos, M; Lima Lopes, J; Beringuilho, M; Ferreira, H; Ferreira, J; Freitas, A; Morais, C
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Platypnea-orthodeoxia syndrome (POS) is an uncommon condition characterized by dyspnoea and hypoxemia in the upright position that improves with recumbency.1 Possible causes are intracardiac shunt, pulmonary arteriovenous shunt, and V/Q mismatch.1, 2 Echocardiography is the cornerstone of POS diagnosis, with special focus on atrial septal defect (ASD) morphology and right-to-left shunt confirmation.3 Purpose: To evaluate the clinical and echocardiographic features of patients presenting with POS due to a cardiac cause. Methods: We performed a retrospective analysis of patients diagnosed with POS in our centre between 2015 January and 2021 August. Routine blood tests and transthoracic echocardiogram (TTE) were performed in all patients. Demographics, clinical presentation, blood test results, TTE information, and PFO closure procedure details were recorded. Results: Seven patients were included, 85.7% female (n = 6). The median (IQR) age was 78 (72-85) years. The most prevalent cardiovascular risk factors were hypertension (100%; n = 7) and overweight/obesity (85.7%; n = 6). Two patients (28.6%) had chronic pulmonary disease. The most common symptoms were fatigue and exercise intolerance (n= 5; 71.4%) and the most frequent sign was persistent hypoxemia (n = 7; 100%), although 28.6% (n = 2) patients did not present the typical positional changes in peripheral oxygen saturation. Haemoglobin levels [14.1 (13.3-15.2)] were within the normal range and serum NTproBNP levels [656 (287-1196)] were slightly elevated. Left ventricle function was preserved in all patients; right ventricle morphology and function were normal in 85.7% (n = 6) patients, low probability of pulmonary hypertension in TTE was found in 85.7% (n = 6), and exuberant Eustachian valve was observed in 14.3% (n = 1). All patients presented atrial septal hypermobility, 87.5% (n = 6) meeting atrial septal aneurysm criteria. Patent foramen ovale was found in 85.7% of patients (n = 6) and ostium secundum ASD in 14.3% (n = 1). POS precipitating factors were aortic root dilation (28.6%; n = 2), chest trauma (14.3%; n = 1), right hip arthroplasty (14.3%; n = 1), atrial septal stretching regarding right volume overload (14.3%; n = 1). The underlying mechanism was unknown in 28.6% (n = 2) of patients. ASD closure was performed in 57.1% (n = 4) of patients: 75% (n = 3) showed residual shunt, but clinical improvement was reported by all. No acute complications were described, except for paroxysmal atrial fibrillation (14.3%; n = 1). Conclusion: POS diagnosis depends on high clinical suspicion: the most common manifestations are fatigue and persistent hypoxemia. Typical positional changes in oxygen saturation are not present in all patients. Polycythaemia, right chambers dilation, and pulmonary hypertension are not common. Echocardiography is fundamental for diagnosis, allowing right-to-left shunt confirmation and ASD morphology evaluation to outline a successful closure procedure.